Effect of Commercial Probiotics Addition in Feed on the growt of Sea Bass (Lates calcalifer) (Jurnal Intek Akuakultur, 2020)
This study was to determined the best dosege of EM4 probiotics and the effect of added EM4 probiotics in feed for the growth of Sea Bass. This research was held on September 2019 at the Riau Islands Dompak Departmen of Marine and Fisheries Resources. The method was used Completed Random Design with 4 treatments and 3 replications P0 = without probiotics P1 = addition of EM4 probiotics 3 ml / kg P2 = addition of EM4 probiotics 6 ml / kg P3 = addition of EM4 probiotics 9 ml / kg. Using data analysis was used One-Way ANOVA and results showed that the addition of probiotics to the feed gave the best results in treatment C (9 ml / kg), where the growth of daily weight (0.45 ± 0.03 g), daily length growth (0 , 06 ± 0.00 cm), absolute weight growth (20.27 ± 1.54 g), absolute length growth (2.91 ± 0.30 cm), feed efficiency (39.24 ± 4.79%), conversion ratio feed (2.78 ± 0.38%) and survival (100.00, ± 0.00%) better than other treatments.